Nurses in post-operative heart surgery: professional competencies and organization strategies - Ana Paula Azevedo Santos; Silvia Helena Henriques Camelo; Fabiana Cristina dos Santos; Laura Andrian Leal; Beatriz Regina da Silva (SciELO, 2016)
Abstract OBJECTIVE To analyze nurses' competencies with regard to their work in post-operative heart surgery and the strategies implemented to mobilize these competencies. METHOD This was an exploratory study with a qualitative approach and a methodological design of collective case study. It was carried out in three post-operative heart surgery units, consisting of 18 nurses. Direct observation and semi-structured interviews were employed to collect data. Data were construed through thematic analysis. RESULTS nine competencies were found, as follows: theoretical-practical knowledge; high-complexity nursing care; nursing supervision; leadership in nursing; decision making; conflict management; personnel management; material and financial resources management; and on-job continued education. Organizational and individual strategies were employed to develop and improve competencies such as regular offerings of courses and lectures, in addition to the individual pursuit for knowledge and improvement. CONCLUSION the study is expected to lead future nurses and training centers to evaluate the need for furthur training required to work in cardiac units, and also the need for implementing programs aimed at developing the competencies of these professionals.